2001
DOI: 10.1128/aem.67.12.5585-5592.2001
|View full text |Cite
|
Sign up to set email alerts
|

Isolation, Characterization, and Polyaromatic Hydrocarbon Degradation Potential of Aerobic Bacteria from Marine Macrofaunal Burrow Sediments and Description ofLutibacterium anuloederansgen. nov., sp. nov., andCycloclasticus spirillensussp. nov

Abstract: Two new polyaromatic hydrocarbon-degrading marine bacteria have been isolated from burrow wall sediments of benthic macrofauna by using enrichments on phenanthrene. Strain LC8 (from a polychaete) and strain M4-6 (from a mollusc) are aerobic and gram negative and require sodium chloride (>1%) for growth. Both strains can use 2- and 3-ring polycyclic aromatic hydrocarbons as their sole carbon and energy sources, but they are nutritionally versatile. Physiological and phylogenetic analyses based on 16S ribosom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
65
0
2

Year Published

2005
2005
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 107 publications
(67 citation statements)
references
References 34 publications
0
65
0
2
Order By: Relevance
“…Microbial communities collected in marine macrofaunal burrows have also been reported to be highly species-specific (Steward et al 1996). Further, Chung & King (2001) discovered 2 previously unidentified marine bacterial species residing in burrow-wall sediment of the polychaete Nereis virens and the mussel Mya arenaria. Both bacterial species were able to use PAHs as their sole carbon source, but with different efficiency.…”
Section: Burrow Sedimentmentioning
confidence: 96%
“…Microbial communities collected in marine macrofaunal burrows have also been reported to be highly species-specific (Steward et al 1996). Further, Chung & King (2001) discovered 2 previously unidentified marine bacterial species residing in burrow-wall sediment of the polychaete Nereis virens and the mussel Mya arenaria. Both bacterial species were able to use PAHs as their sole carbon source, but with different efficiency.…”
Section: Burrow Sedimentmentioning
confidence: 96%
“…dieselolei [10], C. pugetii [11], and C. oligotrophus [12], and more nutritionally versatile species with less restricted substrate profiles, like A. venustensis and C. spirillensus [9,13]. The three other genera of the OHCB group, despite being represented by numerous members, are monophyletic and represented by the three type species Oleiphilus messinensis [14], Oleispira antarctica [15] and Thalassolituus oleivorans [16].…”
Section: Taxonomy Of Obligate Hydrocarbonoclastic Bacteriamentioning
confidence: 99%
“…Organisms analysed so far exhibit features typical of oligotrophic bacteria [43,**44]. The most detailed studies, carried out with C. oligotrophus, have shown that the cytoplasm of this small bacterium is very dilute, with a dry mass per cell 7-8 times lower than that of E. coli, but a DNA content of up to 14% dry weight, which contrasts the value of 2% for E. coli [13,43].…”
Section: Genomic Basis Of Ohcb Ecophysiologymentioning
confidence: 99%
“…Zhao et al, 2009;Shao et al, 2010 , Erythrobacter sp. Chung andKing, 2001;Liu, 2013 , Idiomarina sp. Zhao et al, 2009;Kleinsteuber et al, 2006 and Alcaligenes sp.…”
Section: Discussionmentioning
confidence: 99%